Los factores limitantes de la internacionalización de las pymes textil, cuero, calzado e industria marroquinera colombianas (2015)
This article is intended to contribute to the understanding of the limitations that the Colombian SMEs have for insertion in the international trade and is based on the co-research “Competitiveness strategies for the internationalization of SMEs in the subsectors of textile, leather, footwear and the leather goods industry, “which was led by those who write. In it are gathered some of the main theories that support the internationalization of economies and particularly of the SMEs and gives, from the application of a survey, empirical criteria that explains some of the reasons that the SMEs’ entrepreneurs in the subsectors under study, consider the main constraints for its expansion to foreign markets.